Strategic analysis of India’s river linking project - Amarasinghe, Upali A. (CGIAR Challenge Program on Water and Food, 2009)
“The Strategic Analysis of India’s National River Linking Project”: In 2005, the International Water Management Institute (IWMI) and the Challenge Program on Water and Food (CPWF) started a three-year research study on “Strategic Analysis of India’s River Linking Project”. The primary focus of the IWMI-CPWF project is to provide the public and the policy planners with a balanced analysis of the social benefits and costs ofthe National River Linking Project (NRLP). The project consists of research in three phases. Phase I analyzed India’s water future scenarios to 2025/2050 and related issues. Phase II, analyses how effective a response NRLP is, for meeting India’s water future and its social costs and benefits. Phase III contributes to an alternative water sector perspective plan for India as a fallback strategy for NRLP.